2020
DOI: 10.1111/jocn.15436
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of young women who underwent female genital mutilation/cutting

Abstract: Aim and objectives: To describe the FGM/C experiences of young women living in Nigeria. Background: Globally, several activities have been targeted at ending female genital mutilation/cutting (FGM/C). However, the practice is ongoing, especially in countries such as Nigeria, which is reported to be having a population boom. Therefore, there is a need to investigate the FGM/C experiences of young women in such countries so that efforts towards ending it can be accelerated using evidence-based, community-led int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Female Genital Mutilation/Cutting (FGM/C) is a "surgical procedure involving partial or total removal of the external female genitalia or other injury to the female genitalia organs, whether for cultural or any other non-therapeutic reasons" [1,2]. FGM/C has received considerable attention in both local and international discussions due to its dehumanizing act and violation of women's health rights [3][4][5][6][7]. About 200 million women and girls have undergone FGM/C, and additional 68 million girls will undergo the cutting before 2030 if appropriate and timely interventions are not implemented [8].…”
Section: Introductionmentioning
confidence: 99%
“…Female Genital Mutilation/Cutting (FGM/C) is a "surgical procedure involving partial or total removal of the external female genitalia or other injury to the female genitalia organs, whether for cultural or any other non-therapeutic reasons" [1,2]. FGM/C has received considerable attention in both local and international discussions due to its dehumanizing act and violation of women's health rights [3][4][5][6][7]. About 200 million women and girls have undergone FGM/C, and additional 68 million girls will undergo the cutting before 2030 if appropriate and timely interventions are not implemented [8].…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that 1 in 500 victims die from FGM [14,15]. Some victims of this practice suffer death as a result of blood loss and severe infections.…”
Section: Complications Of Female Genital Mutilationmentioning
confidence: 99%
“…Despite the effects of circumcision, some still support the practice (4). According to studies, damage to the clitoris following circumcision causes a woman to have less sexual arousal and not be easily sexually aroused, thus increasing their ability to remain a virgin before marriage and delity to their husbands after marriage (5).…”
Section: Introductionmentioning
confidence: 99%